Impact of Postnatal Antibiotics and Parenteral Nutrition on the Gut Microbiota in Preterm Infants During Early Life. Issue 4 (26th August 2019) - Jia, Jie; Xun, Pengcheng; Wang, Xinling; He, Ka; Tang, Qingya; Zhang, Tian; Wang, Ying; Tang, Wenjing; Lu, Lina; Yan, Weihui; Wang, Weiping; Hu, Tianyi; et al.
Abstract: Background: The early‐life gut microbiota, which is critically important for the long‐term health of infants, is normally sensitive to perturbations, especially in preterm infants. However, how the gut microbiota develops and what key factors affect the preterm gut microbiota remain largely unknown. We hypothesized that preterm microbial dysbiosis exists from the beginning after birth, and microbial alteration is associated with parenteral nutrition and antibiotic therapy interventions. Methods: Fecal samples were collected from fifty‐one preterm and fifty full‐term vaginally delivered (FTVD) infants at 7 time points for 90 days after birth. The microbial profiles of 558 fecal DNA samples were analyzed by sequencing their 16S ribosomal RNA amplicons. A random‐effects generalized least square regression was used to identify factors that influence the bacterial composition over time. Results: The altered gut microbiota in preterm infants existed from the meconium, having significantly lower levels of Escherichia‐Shigella than those in FTVD infants. The developmental trajectories of 7 predominant bacterial groups successfully fitted with exponential/linear function curves (R 2, 0.921–0.993) in both groups. By day 90, depleted levels of Bacteroides and Parabacteroides and an overabundance of Peptoclostridium were characteristic of the preterm group. The prolonged use of antibiotics and parenteral nutrition had significant adverse effects on the Lactobacillus and Bifidobacterium levels in preterm infants. Moreover, gestational age, sex, and birth weight were factors impacting specific genera in preterm infants. Conclusion: The early‐life microbial composition and functions were markedly different in preterm infants, being associated with the prolonged use of postnatal antibiotics and parenteral nutrition.